powers are usually written this way...
(h+k)(h^2 - 2hk + 3k^2)
which becomes
h^3 -2h^2k + 3hk^2 + kh^2 - 2hk^2 + 3k^3
= h^3 - h^2k + hk^2 + 3k^3
Okay, I'm working with ultiplying Polynomials, and I just can't figure this one out! Here it is:
(h+k)(h squared-2hk+3k squared)
haha, I don't know how to make an exponent on the computer :-), but anyway, please help me figure it out!
4 answers
oh, I tried to solve it and got 3hk^2+h^3 I'm guessing that's wrong?
I solved it like this: h^3-2hk^2+3hk^2+1hk^2-2hk^2+3hk^2=3hk^2+h^3
for the terms inside
-2h^2k + h^2k = -h^2k
and
3hk^2 - 2hk^2 = hk^2
look at my expansion and compare it to yours,
a term in hk^2 is not the same as a h^2k term.
-2h^2k + h^2k = -h^2k
and
3hk^2 - 2hk^2 = hk^2
look at my expansion and compare it to yours,
a term in hk^2 is not the same as a h^2k term.